Nationalism, law and statelessness : grand illusions in the Horn of Africa - Campbell, John (John R.) (Milton Park, Abingdon, Oxon : Routledge, 2014)
In 1998 a bloody war erupted in The Horn of Africa between Ethiopia and Eritrea. During the war Ethiopia arrested and expelled 70,000 of its citizens, and stripped another 50,000-plus of their citzenship on the basis of their presumed ethnicity. Nationalism, Law and Statelessness: Grand Illusions in the Horn of Africa examines the events which led up to the war, documents the expulsions and denationalisations that took place and follows the flight of these stateless Ethiopians out of the Horn into Europe.
The core issue examined is the link between sovereignty and statelessness as this plays out in The Horn of Africa and in the West. The book provides a valuable insight into how nations create and perpetuate statelessness, the failure of law, both national and international, to protect and address the plight of stateless persons, and the illusory nature of nationalism, citizenship and human rights in the modern age. The study is one of a very few which examines the problem of statelessness through the accounts of stateless persons themselves. -- Publisher.
Nationalism, the 1998-2000 Ethiopia-Eritrea war and the denationalisation of Eritreans -- Politics, law and the limitations of international arbitration at the Hague -- Flight from the Horn : transiting Africa to find refuge -- The illusion of citizenship and of return : politics and persecution in the Horn -- The illusion of refuge : the search for asylum and the failure of international law --'Bare life' : the vulnerability and political significance of stateless persons -- Conclusion.
Includes bibliographical references (pages 198-210) and index.
Keywords: Refugees -- Legal status, laws, etc. -- Ethiopia; Refugees -- Legal status, laws, etc. -- Eritrea; Refugees -- Horn of Africa